2020
DOI: 10.1111/gcb.15193
|View full text |Cite
|
Sign up to set email alerts
|

Snow melt stimulates ecosystem respiration in Arctic ecosystems

Abstract: Cold seasons in Arctic ecosystems are increasingly important to the annual carbon balance of these vulnerable ecosystems. Arctic winters are largely harsh and inaccessible leading historic data gaps during that time. Until recently, cold seasons have been assumed to have negligible impacts on the annual carbon balance but as data coverage increases and the Arctic warms, the cold season has been shown to account for over half of annual methane (CH 4) emissions and can offset summer photosynthetic carbon dioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…The difference in CH 4 emissions during spring thaw and autumn freeze can be explained by the different freeze-thaw and thaw-freeze processes ( Figure 6). During autumn freeze, soil freezes downward from the top soil layers and upward from the permafrost surfaces (Arndt et al, 2020;Bing et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference in CH 4 emissions during spring thaw and autumn freeze can be explained by the different freeze-thaw and thaw-freeze processes ( Figure 6). During autumn freeze, soil freezes downward from the top soil layers and upward from the permafrost surfaces (Arndt et al, 2020;Bing et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Soil water migrates upward and downward to freezing fronts leaving "air pockets" in between, even in the inundated active layer (Arndt et al, 2020;Bing et al, 2015;Shoop & Bigl, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are large uncertainties as to whether the Arctic tundra is currently an annual source or sink of CO 2 (McGuire et al, 2012). Recent studies have highlighted the importance of CO 2 emissions during the long winter and shoulder season periods, which may offset CO 2 gains by Arctic ecosystems during the short growing season Oechel et al, 2014;Euskirchen et al, 2017;Arndt et al, 2020). Long-term trends in winter CO 2 fluxes are generally difficult to ascertain due to a scarcity of year-round measurements, but several studies have suggested winter CO 2 emissions are changing.…”
Section: Introductionmentioning
confidence: 99%